Acute venous thromboembolism in patients with brain cancer: clinical course - Becattini, Cecilia; Giustozzi, Michela; Portillo, José; Fernández-Capitán, Carmen; Lobo, José Luis; Peris, Ma Luisa; Font, Carme; Grange, Claire; Weinberg, Ido; Monreal, Manuel; RIETE Investigators; Bosevski, Marijan; et al. (Elsevier BV, 2023)
Patients with brain cancer have been excluded or were underrepresented in studies on the treatment of venous thromboembolism (VTE), mainly due to the fear of intracranial hemorrhage (ICH).